ANALISIS PERAN HAKIM DALAM MENEGAKKAN KEADILAN DAN KEMANUSIAAN - Cahyani, Gisella Tiara; Azzahra, Najwa Maulida; Lubis, Rania Faradita; Surya Kusuma, Eduardus Eka (LPPM Universitas Bina Bangsa, 2025)
The role of judges in upholding justice and humanity is the core of a functioning legal system. Judges have the responsibility to uphold justice, provide fair legal protection to all individuals, and ensure that human rights are respected during the judicial process. In fulfilling their duties, judges must possess integrity, intelligence, and sensitivity to moral values. They must also be able to withstand political, economic, and social pressures that may affect their independence. Furthermore, judges need to understand and apply the law wisely according to the social, cultural, and political contexts. Amidst the complexity of globalization and technological advancements, the role of judges becomes increasingly important in ensuring that justice and humanity are upheld in a changing legal system. Therefore, judges must continuously improve themselves through education, training, and self-reflection to better fulfill their duties effectively.